2009
DOI: 10.1177/0003319709335908
|View full text |Cite
|
Sign up to set email alerts
|

Wall Shear Stress Measurement Using Phase Contrast Magnetic Resonance Imaging with Phase Contrast Magnetic Resonance Angiography in Arteriovenous Polytetrafluoroethylene Grafts

Abstract: Purpose The purpose of the present article was to determine the changes in luminal vessel area, blood flow, and wall shear stress in both the inflow artery and the venous stenosis of arteriovenous polytetrafluoroethylene (PTFE) grafts. Methods and materials Polytetrafluoroethylene grafts were placed from the carotid artery to the ipsilateral jugular vein in 8 castrated juvenile male pigs. Contrast-enhanced magnetic resonance angiography (MRA) with cine phase-contrast magnetic resonance imaging (MRI) was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
(66 reference statements)
0
15
0
Order By: Relevance
“…Two studies used contrast-enhanced MR angiography and 2D PC-MRV to investigate temporal changes in the geometry, flow, and WSS in pigs following placement of PTFE grafts. 26,27 Krishnamoorthy et al 17 applied CFD to simulate complete WSS profiles in two configurations of native AVFs created in pigs. They found an inverse correlation between mean WSS at the time of AVF placement and the degree of luminal stenosis at 42 days post-surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies used contrast-enhanced MR angiography and 2D PC-MRV to investigate temporal changes in the geometry, flow, and WSS in pigs following placement of PTFE grafts. 26,27 Krishnamoorthy et al 17 applied CFD to simulate complete WSS profiles in two configurations of native AVFs created in pigs. They found an inverse correlation between mean WSS at the time of AVF placement and the degree of luminal stenosis at 42 days post-surgery.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 However, very little data describing the changes in humans is available. Description of changes in estimated WSS and vessel diameter at specific locations was obtained by US studies, 5 but no 3D analysis was provided.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that there is an increase in mRNA of ADAMTS-1 from human umbilical vein endothelial cells (HUVEC) and cardiac microvascular endothelial cells which have been exposed to shear stress [30]. Increased shear stress has been hypothesized as a potential etiology for hemodialysis graft failure [7, 31, 32]. In the present study, we observed significant increase in gene expression of ADAMTS-1 at the venous stenosis when compared to control vein by day 7.…”
Section: Discussionmentioning
confidence: 99%
“…The high flow momentum entering the vein at an unfavorable angle is thought to be one of the major causes for IH of the vein. 16,17 The Venaflo prosthesis was developed to decrease the high wall shear forces. 8 This graft uses a venous anastomotic cuff that effectively reduces the shear forces present near the venous wall.…”
Section: Discussionmentioning
confidence: 99%